Correction: Breath odor-based individual authentication by an artificial olfactory sensor system and machine learning. Issue 44 (20th May 2022) - Jirayupat, Chaiyanut; Nagashima, Kazuki; Hosomi, Takuro; Takahashi, Tsunaki; Samransuksamer, Benjarong; Hanai, Yosuke; Nakao, Atsuo; Nakatani, Masaya; Liu, Jiangyang; Zhang, Guozhu; Tanaka, Wataru; Kanai, Masaki; et al.
Abstract : Correction for 'Breath odor-based individual authentication by an artificial olfactory sensor system and machine learning' by Chaiyanut Jirayupat et al., Chem. Commun ., 2022, DOI: ; https://doi.org/10.1039/D1CC06384G .